2018
DOI: 10.11604/pamj.2018.30.224.13947
|View full text |Cite
|
Sign up to set email alerts
|

Dépistage néonatal du déficit en glucose 6 phosphate déshydrogénase (G6PD) en Mauritanie

Abstract: IntroductionUne étude transversale et descriptive qui vise l'identification des facteurs de risques associés au déficit en G6PD, sa fréquence et sa distribution géographique à Nouakchott dans l'objectif de fournir des informations utiles pour le contrôler. Comme cette maladie n'a jamais été étudiée auparavant en Mauritanie, nous avons cherché à définir le profil épidémiologique et la charge de morbidité du déficit en G6PD chez une population de nouveaux nés dans deux structures de santé de la ville de Nouakcho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…All other ethnic groups are of black African ancestry. Based on this information, as well as on earlier studies carried out in sub-Saharan African countries bordering Mauritania and in Mauritania, it was further hypothesized that some individuals belonging to the ethnic groups of black African descent may carry the African-type G6PD A- genotype [ 4 , 18 , 19 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…All other ethnic groups are of black African ancestry. Based on this information, as well as on earlier studies carried out in sub-Saharan African countries bordering Mauritania and in Mauritania, it was further hypothesized that some individuals belonging to the ethnic groups of black African descent may carry the African-type G6PD A- genotype [ 4 , 18 , 19 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 98%
“…At present, the amount of data available on G6PD genotypes (or phenotypes) in Mauritania is limited to two studies conducted in Nouakchott [ 18 , 19 ]. It is known that G6PD polymorphisms are associated with ethnicity [ 8 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of G6PD deficiency was 11.09%, with a higher prevalence among males (15%) than females (7%). G6PD deficiency was more common in males than females (p-value = 0.007); also, Black children (15%) had a higher prevalence of G6PD deficiency than White children (8%) [27]. AL-Riyami et al studied the prevalence of G6PD deficiency among 6103 Omani households and 6342 children aged 0-5 years.…”
Section: Epidemiology Of G6pd Deficiency In Arab Countries: Key Findingsmentioning
confidence: 99%
“…Mauritania-Mauritania is an extremely poor country with a developing healthcare system. Previous studies have confirmed the presence of both G6PD deficiency and HGBs and have supported the concept of NBS as a means of decreasing infant morbidity and mortality [1534][1535][1536]. We are aware of no current efforts to introduce a national NBS program.…”
mentioning
confidence: 97%